An experimental manipulation of negative metacognitive beliefs in non-clinical paranoia: Effects on intrusions and state anxiety. Issue 3 (1st August 2018) - Sellers, Rachel; Wells, Adrian; Morrison, Anthony P.
Metacognitive beliefs implicated in the Self-Regulatory Executive Function (S-REF) model (Wells & Matthews, 1994, 1996) have demonstrated significant positive relationships with experiences of psychosis. This study aimed to investigate the effect of manipulating metacognitive beliefs relating to the uncontrollability and danger of thoughts on paranoia frequency and negative affect in a non-clinical sample. Seventy-six students participated in a randomised experiment. All participants were falsely informed they were taking part in an EEG study about thought processes in paranoia. Following a paranoia induction, participants in the experimental condition were told that the EEG could detect paranoid thoughts and may make a loud noise in response to detecting them; participants in the control condition were told the EEG could detect paranoid thoughts and may make a loud noise at random. Validity checks confirmed the paranoia prime was effective and there was a significant change in metacognitive beliefs following the manipulation. Overall no significant differences between the two groups on measures of intrusions or anxiety emerged following the manipulation. However, changes in physiological anxiety approached significance. The results demonstrate it is feasible to manipulate metacognitive beliefs and induce paranoia. A recommendation for further research to use a refined paradigm with a clinical sample is discussed.